Pelatihan Pembuatan Gula Semut Dalam Rangka Meningkatkan Perekonomian Masyarakat Desa Labissa - Nur Nur Fisabilianti; Andi Badli Rompegading; Syamsu Rijal; Muhammad Nasir; Ahmad Yani; Rizal Irfandi; Muhammad Arafah (Education and Talent Development Center Indonesia, 2024)
This ant sugar Making Training From Nira Lontar has increased the knowledge and skills of the community to manage and optimize ezisting Natural Resources (SDA) and Human Resources (SDM),in order to improve the economy of the Labissa Village community.by using the following methods and stages;1) Presentation of material on processing brown sugar (Nira Lontar) into Ant Sugar,2)Demonstration on processing brown sugar (Nira Lontar) into Ant Sugar, 3) Product Packing Training 4)Evaluation of the result of the training. This research was carried out in November 2023 in Labissa Village,Ajangale District,Bone Regency.Survey and interview result of 85% of training participants responded positively to this training.25 training felt satisfied and enthusiastic about the activities carried out.